Strategi Komunikasi Organisasi Studi Kasus pada Karang Taruna Desa Sukarame Kecamatan Pacet, Kabupaten Bandung, Jawa Barat 40385: Pengabdian - Vera Martikasari; Wanda Sofianti; Husni Munawar; Annisa Zahra Rahmayati; Silvia Nurfadilah; Siti Nur Jamilah; Syahla Nur Fikriyyah; Anjani; Raisa Ratna Khodijah; Jaomal Komara; Djufran D Hi Kasim (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research investigates the organizational communication strategies implemented in Karang Taruna RW 005 Babakan, Sukarame Village, Pacet District, Bandung Regency, West Java. Communication is not merely the transmission of information but a fundamental mechanism in shaping organizational culture, maintaining member engagement, and ensuring program sustainability. Youth organizations in rural contexts often struggle with message clarity, hierarchical distortion, limited digital literacy, and inconsistent information management. Adopting a qualitative single-case study, this research combines in-depth interviews with youth leaders and members, focus group discussions, participatory observation during meetings and events, and document analysis (minutes, proposals, financial reports, and social media content). The findings reveal that communication practices in Karang Taruna RW 005 are multi-layered: interpersonal (face-to-face mentoring, leader–member dialogue), group (meetings, deliberations, consensus-building), and digital communication (WhatsApp groups, social media outreach). Applying Lasswell’s communication model and Shannon–Weaver’s linear model, the study identifies how communication effectiveness depends on message clarity, channel selection, and feedback responsiveness. Communication barriers include overlapping information channels, limited documentation habits, and uneven participation across gender and age. Enablers consist of strong community trust, cultural norms of gotong royong, and the emerging digital competence among youth. This paper proposes a five-pillar communication strategy—clarity, inclusivity, transparency, technology adoption, and continuous evaluation—that enhances organizational resilience. The study contributes to organizational communication literature by contextualizing global theories within rural Indonesian youth organizations and offers a replicable roadmap for community-based organizations across similar settings.